2022
DOI: 10.3390/ijms23031288
|View full text |Cite
|
Sign up to set email alerts
|

LCZ696 Protects against Diabetic Cardiomyopathy-Induced Myocardial Inflammation, ER Stress, and Apoptosis through Inhibiting AGEs/NF-κB and PERK/CHOP Signaling Pathways

Abstract: The present study is designed to determine the effect of LCZ696 on DCM in rats and investigate the underlying mechanism involved. Diabetes was induced by feeding rats with a high-fat diet for six weeks following a single injection of STZ (30 mg/kg). Diabetic rats were divided into three groups (n = 10). LCZ696 and valsartan treatment was started two weeks after diabetic induction and continued for eight weeks. At the end of the treatment, serum and cardiac tissues were analyzed by RT-PCR, Western blot, and ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…Our study showed that the expression of eyeball AGEs in DM mice was also positively correlated with AGE levels in the serum and kidneys. This is similar to the results of previous studies (9).We also found that AGEs promoted renal pathological damage and podocyte injury in DKD mice through the NF-kB signaling pathway, which was consistent with the results of Coughlan MT et al (21,25). The characteristics of AGEs deposited in multiple tissues and cells in the present study are consistent with these findings from previous studies, which offers a partial explanation for the concept of "detection of AGEs through noninvasive lenses to reflect kidney damage".…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that the expression of eyeball AGEs in DM mice was also positively correlated with AGE levels in the serum and kidneys. This is similar to the results of previous studies (9).We also found that AGEs promoted renal pathological damage and podocyte injury in DKD mice through the NF-kB signaling pathway, which was consistent with the results of Coughlan MT et al (21,25). The characteristics of AGEs deposited in multiple tissues and cells in the present study are consistent with these findings from previous studies, which offers a partial explanation for the concept of "detection of AGEs through noninvasive lenses to reflect kidney damage".…”
Section: Discussionsupporting
confidence: 93%
“…AGEs contain substances with fluorescent properties, such as pentosidine and imidazoline. Thus, AGEs in the human body can be detected by special instruments without specific exogenous labeling.AF of the lens, skin tissue and serum can represent the blood glucose level in DM patients to a certain extent (23)(24)(25)(26)(27)(28).Lens AF measurement is a noninvasive and rapid method that can be readily used in doctors' offices that indirectly shows AGE accumulation in the natural lens of the eye, most commonly due to DM (28,29). The results of Frederick Cahn et al showed that lens autofluorescence levels were highly predictive of diabetes and that progressively higher fluorescence deviations were observed in prediabetes, type 2 diabetes, and type 1 diabetes (30).However, the adoption of noninvasive AGEs technology to detect and evaluate DKD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional mitochondria can cause increased ROS production and the release of factors that favor cell death, such as cytochrome C (an apoptosis-inducing factor) and Smac/DIABLO (the second activator of caspases) [21,74,81,82], and the induction of pyroptosis, characterized by activation of the inflammasome through the activation of caspase 1 and pro-inflammatory cytokines [83][84][85], although this sub-type of programmed cell death has previously been associated with infection by intracellular pathogens. Various ROS scavengers or antioxidants reduced cardiomyocyte death and attenuate diabetic heart injury in experimental animal models [81,86].…”
Section: Discussionmentioning
confidence: 99%
“…Sacubitril/valsartan significantly downregulates advanced glycation end products formation and receptor for advanced glycation end-product (RAGE) expression while decreasing C/EBP homologous protein (CHOP) and phosphorylated PKR-like endoplasmic reticulum kinase (PERK) expression levels in rats with diabetic cardiomyopathy (DCM) ( 26 ). This leads to improved endoplasmic reticulum (ER) stress and DCM-induced apoptosis.…”
Section: Mechanisms Of Action Of Sacubitril Valsartan: Experimental E...mentioning
confidence: 99%